Latar Belakang Pendidikan Guru Biologi dalam Implementasi Model Pembelajaran Inkuiri dan Teknik Penilaian Inkuiri - Purbowati, Dwi (Universitas Nusantara PGRI Kediri, 2020)
The research objectives to determine the implementation of inquiry learning models and inquiry assessment techniques by biology teachers based on the teacher's educational background. This study was qualitative descriptive approach with a survey method. The research was conducted at SMAN Surakarta with a research sample of 7 biology teachers who teach in class X. The research instruments used were observation sheets, questionnaire sheets, questionnaire sheets, documentation sheets, and interview guidelines. The results showed that biology teachers with educational backgrounds, with master degree education level, and private universities able to implement inquiry learning models and inquiry assessment techniques.